1987
DOI: 10.1002/ar.1092170407
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase in prenatal rat heart: A marker for the early development of the cardiac conductive tissue?

Abstract: In rat embryos, acetylcholinesterase (AChE, EC 3.1.1.7) activity is present in a continuous sleeve of myocytes that extends from the myocardium that is adjacent to the atrioventricular endocardial cushions via the ventricular trabeculae to the outflow tract. No activity is found in the atrial roof, in the ventricular walls and in the interventricular septum except for its subendocardial surface. AChE-positive cells are first identified in 11-day rat embryos, while the prototypical distribution is best demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Embryos and fetuses were obtained from timed pregnant rats as described before.14 Hearts from rats at 13,14,16, and 20 embryonic days (EDs), from neonates (ED 22), and from adult rats were studied. Because the monoclonal antibody against connexin32 was raised in rats, it was decided to study the expression pattern of this protein in mice.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryos and fetuses were obtained from timed pregnant rats as described before.14 Hearts from rats at 13,14,16, and 20 embryonic days (EDs), from neonates (ED 22), and from adult rats were studied. Because the monoclonal antibody against connexin32 was raised in rats, it was decided to study the expression pattern of this protein in mice.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Nicholson (SUNY, Buffalo, N.Y.) kindly provided us with two additional rabbit antibodies. The first antibody was raised against amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the amino terminal domain of connexin43, and the second antibody was raised against amino acids 302-319 at the carboxyl terminal domain of connexin43. The latter antibody was affinity-purified.…”
Section: Antibodiesmentioning
confidence: 99%
“…We found that expression of Cx40 and Na v 1.5 was drastically reduced in the VCS after removal of Tbx5 ( Figure 5). The proximal AV bundle and distal AV bundle/bundle branches were identified by their anatomic location, acetylcholinesterase activity (12,(17)(18)(19), and contactin-2 expression (20). Tbx5 fl/fl controls demonstrated high Cx40 and Na v 1.5 expression throughout the molecularly defined VCS, whereas Tbx5 minKCreERT2 animals demonstrated dramatic Values are mean ± SD.…”
Section: Figurementioning
confidence: 99%
“…No CX40 has been detected in the sinoatrial or atrioventricular nodes, which are known to be CX40 deficient (Gros et al, 1994). Different markers that codistribute with the adult conduction system during its differentiation have been described: IC8 (Gorza and Vitadello, 19891, Leu-7 or HNKl (Ikeda et al, 1990;Nakagawa et al, 19931, aMHC/PMHC (De Groot et al, 1989), and AChE (Lamers et al, 1987). In contrast to these markers, CX40 is still expressed in adult heart and is known as a constitutive protein of the junctional channels directly involved in the conduction of the electrical impulse in the VCS.…”
Section: Distribution Of Cx40 In the Conduction Systemmentioning
confidence: 99%